Penerapan Model Discovery Learning Materi Q.S At-Tin untuk Meningkatkan Prestasi Belajar Siswa Sekolah Dasar - Sutriyani, Sutriyani; Amin, Alfauzan (Jurnal Indonesia Pendidikan Profesi Guru, 2025)
Background: In recent years, the shift from teacher-centered to student-centered learning has emphasized the need for innovative teaching models that actively involve students in the learning process. One such model is discovery learning, which encourages students to explore, investigate, and construct their own understanding. Objective: This study aims to determine the improvement in student learning achievement following the implementation of the discovery learning model in Islamic religious education and character education subjects. Method: The research employed a Classroom Action Research (CAR) approach and was conducted at SDN 05 Selagan Raya in 2023. Data collection techniques included observation and tests, and data analysis was based on the students’ learning mastery scores. The study followed four implementation stages: (1) planning, (2) acting, (3) observing, and (4) reflecting. Result: The findings showed that the use of the discovery learning model improved learning efficiency and student achievement. Students were more actively engaged in the learning process, which led to better understanding and retention of the material. Conclusion: The application of the discovery learning method is effective in enhancing learning outcomes and student motivation. It provides opportunities for students to be directly involved in problem-solving and to discover new concepts, making the learning process more meaningful. Contribution: This study offers practical insights for educators by highlighting the discovery learning model as an effective instructional strategy. It not only improves student achievement but also promotes active learning and motivation, benefiting both students and teachers in the learning process.